Telling Multispecies Stories from the Anthropocene: Review of Anna Tsing, Heather Swanson, Elaine Gan, Nils Bubandt, eds. Arts of Living on a Damaged Planet: Ghosts and Monsters of the Anthropocene - Otjen, Nathaniel (Humanimalia, 2018)
Anna Tsing, Heather Swanson, Elaine Gan, Nils Bubandt, eds. Arts of Living on a Damaged Planet: Ghosts and Monsters of the Anthropocene. Minneapolis: University of Minnesota Press, 2017. 368 pp. 27.95 pbk, 112 hc.